EVALUATING ROLE-PLAY INSTRUCTION TO IMPROVE MAHARAH KALAM: A MIXED-METHODS - Nagif, Nagif; Tarmizi, Ahmad; Nurani, Qoim (CV. TOTUS TUUS, 2026)
Effective Arabic learning requires innovative methods that are able to improve students' communicative skills, especially in speaking skills (Maharah Kalam) which are often a challenge at the madrasah level. This study aims to determine the effectiveness of the application of the Role Play method on increasing the Maharah Kalam of grade VII students at MTs Ar-Riyadh Pangkalan Balai. This study uses a mixed method method by combining quantitative and qualitative data through a one group pretest–posttest design, where all students receive learning treatment using the Role Play method. The results of the study show that the Role Play method has a significant positive influence on improving students' speaking skills. This can be seen from the increase in the average score from 64.90 in the pretest to 87.80 in the posttest, with a difference of 22.90 points and a significance value of p < 0.001, which confirms the existence of a very statistically significant increase. These findings are in line with Vygotsky's scaffolding theory which emphasizes the importance of social interaction in language acquisition, as well as the theory of Communicative Language Teaching (CLT) which makes language production the core of learning. Thus, Maharah Kalam learning based on Role Play is considered effective in increasing students' fluency in speaking, courage, and activeness, and is feasible to be applied as a strategy to improve the quality of Arabic learning in madrasas.